Student’s Difficulties in Using Transition Signals in Writing Descriptive Paragraph of The Second Year Students of SMP Gajah Mada Medan - Rosdiana Rajagukguk (English Education Department at FKIP Nommensen University, 2023)
This study attempt to discuss student’s difficulties use transition signals when writing descriptive paragraph of SMP Gajah Mada Medan sophomores. The subject of the research is to know the types of transition signals that are difficult for the students to use in writing descriptive paragraphs. The researcher wants to discover the dominant types of transitional signs that are difficult for students to use when writing descriptive paragraphs. The population for the research was 18 second-years SMP Gajah Mada Medan students. The study used descriptive qualitative research. The result of the research showed that there were four types of students’ difficulties in using transition cues when writing descriptive paragraphs, namely: additional idea, opposite idea or contrast, example and cause effect. The dominant type of transition signals that are difficult for students to use when writing descriptive paragraphs was cause and effect with 9 cases (33,3%). This thesis is suggested to students and teachers of the English department as a source of valuable knowledge and information on students’ difficulties in using transition signals.